Exploring information technology governance in a Malaysian public university: providers' perspectives - Ajayi, Binyamin Adaniyi; Hussin, Husnayati (2014)
There has been dearth of studies on how universities, in developing nations, govern their information technology (IT) to leverage the business goals of teaching and learning, research and administration. The purpose of this paper is to present how a public university governs IT and learn from “over the years” experiences to improve disposition to IT. This study view IT governance (ITG) as the desirable IT behaviour deliberately adopted by organisation’s stakeholders to ensure continuous IT performance. The study, using the qualitative method, the use of interview as an instrument of data collection and the university’s document were explored to compare what has changed in the governance of IT over time. It, at different times, sought audience with two IT Directors in succession. Analysis of the data shows how the role of IT has changed over time and what has been learnt in the implementation of the ITG paradigm in a university setting. The report shows how the involvement of the management has improved ITG. The paper represents a systemic account on ITG evolution and its application in the Malaysian context